Validation of a methane oxidation biosystem design methodology using numerical modeling - Dulac, Yohan; Nelson, Brienne R.; Zytner, Richard G.; Cabral, Alexandre R. (Frontiers in Environmental Science, 2024)
Methane oxidation biosystems (MOBs) are cost effective engineered systems capable of catalyzing the transformation of CH4 into CO2 biotically, thereby mitigating emissions from landfills. In this study we validate how accurately one can predict the hydraulic behaviour of a MOB using numerical modeling. More precisely how one can identify the length of unrestricted gas migration (LUGM), a critical design criterion for effective methane abatement biosystems. Laboratory experiments were conducted to obtain the material properties for a compost mixed with plastic pellets, and sand. With the water retention curve and air permeability function, we predicted the hydraulic performance of a MOB using Hydrus-2D. We then designed and constructed a MOB and monitored several key parameters for 12 months. The validation of the design methodology was conducted using field measurements, while actual climatic data was used as input in numerical modeling. The air permeability function was an appropriate activation function for determining LUGM. Accordingly, the predicted hydraulic behaviour matched the measured hydraulic behaviour reasonably well, validating the proposed procedure.well. This is quite encouraging in terms of the practical value of the procedure proposed herein.